Employment Patterns in OECD Countries. - Nickell, S; Nunziata, L (Centre for Economic Performance, LSE, 2000)
This paper studies the dynamics of labour demand and the determinants of employment rates across the OECD. We find: (i) labour demand adjusts less rapidly when employment protection is more strict and union density is higher; (ii) there is no evidence that overall job turnover is influenced by employment protection; (iii) union density and coverage are negatively related to employment/population ratios, although this effect can be entirely offset by coordination; (iv) strict employment protection laws are strongly associated with lower employment rates for women and young people but have no impact on the rates for prime age men.